James : a novel [large type] - Everett, Percival (Random House Large Print, 2024)
When the enslaved Jim overhears that he is about to be sold to a man in New Orleans, separated from his wife and daughter forever, he decides to hide on nearby Jackson Island until he can formulate a plan. Meanwhile, Huck Finn has faked his own death to escape his violent father, recently returned to town. As all readers of American literature know, thus begins the dangerous and transcendent journey by raft down the Mississippi River toward the elusive and too-often-unreliable promise of the Free States and beyond. While many narrative set pieces of Adventures of Huckleberry Finn remain in place (floods and storms, stumbling across both unexpected death and unexpected treasure in the myriad stopping points along the river's banks, encountering the scam artists posing as the Duke and Dauphin...), Jim's agency, intelligence and compassion are shown in a radically new light. Brimming with the electrifying humor and lacerating observations that have made Everett a "literary icon" (Oprah Daily), and one of the most decorated writers of our lifetime, James is destined to be a major publishing event and a cornerstone of twenty-first century American literature.